Modeling of Bernoulli gripping device orientation when manipulating objects along the arc. (12th March 2018) - Savkiv, Volodymyr; Mykhailyshyn, Roman; Duchon, Frantisek; Mikhalishin, Mykhailo
The objective is to define optimal orientation of gripping device with minimal gripper energy consumption, having preset parameters of manipulator, Bernoulli device, object of manipulation and its path. The division of the arc into three sections—speed-up, steady motion, slowing-down—is presented. The optimal orientation is defined in any point of time on each section, which is defined using inertial and gravity forces as object of manipulation retention force with gripping device. Problem solution for a specific example, providing continuous transportation along the whole path for the object of manipulation, is introduced. The effectiveness of using this method of object transportation along the arc is proved. The energy efficiency of the implementation of the optimization orientation method was 41% for the example given.